Impact of sublingual immunotherapy on specific antibody levels in asthmatic children allergic to house dust mites - (:unkn) unknown (KARGER, 2005)
Objective: To evaluate the clinical outcome and changes in allergen-specific antibodies during sublingual immunotherapy ( SLIT) in house dust mite (HDM)-allergic asthma patients and to compare levels of allergen-specific antibodies in HDM-allergic patients before and after treatment with that of healthy controls. Method: Thirty-one asthma patients allergic to HDM were studied. Patients in groups I ( n = 17) and II ( n = 14) received SLIT with a standardized Dermatophagoides pteronyssinus plus Dermatophagoides farinae 50/50 extract for 6 and 12 months, respectively. A group of healthy children ( n = 8) were enrolled as controls. Patients in both groups were evaluated at the start and at the end of treatment according to daily symptom and medication scores, lung function and skin prick tests, PC20, blood eosinophil count, and Der-p-1-specific IgE, IgA, IgG1 and IgG4 levels. Results: Drug consumption decreased significantly in both groups. Furthermore, PC20 and forced expiratory flow between 25 and 75% of vital capacity of patients in group II improved significantly. Although specific IgA, IgG1 and IgG4 levels did not change throughout the treatment period, total eosinophil count and specific IgE decreased significantly in both groups. According to baseline measurements, specific IgA levels of patients in groups I and II were significantly lower than that of controls. This difference disappeared at the end of the treatment period in both groups. Conclusion: SLIT seems to be effective in ameliorating clinical symptoms, drug consumption and bronchial hyperreactivity, and results in downregulation of Der-p-1-specific IgE production. Furthermore, at the end of SLIT, specific IgA levels, which were decreased compared to healthy controls initially, did no longer differ between patients and controls. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: asthma; house dust mites; specific IgA; sublingual immunotherapy; PLACEBO-CONTROLLED EVALUATION; DOUBLE-BLIND; SWALLOW IMMUNOTHERAPY; ORAL TOLERANCE; RHINITIS; EFFICACY; EXTRACT; TRIAL; SLIT